Inovasi Manajemen Organisasi Kesehatan dalam Meningkatkan Mutu Layanan di Era Digital - Rahmah Dwi Asti; Nadiyah Rahma Dalimunthe; Ajib Atha Syah Putra; Meisa Putri Rangkuty; Findyani Siregar; Latifah syahrani; Adillah Maharani; Dewi Agustina (Universitas Muhammadiyah Manado, 2025)
Innovation in healthcare organization management in the digital era plays a crucial role in enhancing the efficiency, accessibility, and quality of healthcare services. As digital technologies continue to evolve, healthcare institutions are increasingly adopting systems such as Electronic Medical Records (EMR), Hospital Management Information Systems (HMIS or SIMRS), telemedicine platforms, mobile health applications, Big Data analytics, and Artificial Intelligence (AI) to streamline operations and improve patient outcomes. This literature review highlights how the implementation of these technologies can accelerate service delivery, reduce administrative burdens, support data-driven clinical and managerial decision-making, and enable remote healthcare access—particularly beneficial in rural or underserved areas. For instance, EMRs improve the accuracy and availability of patient data, while AI can assist in diagnostics and predictive analytics for disease prevention. However, despite these promising developments, several significant challenges persist. These include limited digital infrastructure in some regions, low levels of digital literacy among healthcare professionals, high implementation and maintenance costs, organizational resistance to technological change, and concerns over data privacy and cybersecurity. Therefore, successful digital transformation in healthcare is not solely dependent on technology itself. It also requires strong organizational readiness, supportive regulatory frameworks, investment in workforce training and development, and effective change management strategies. Collaborative efforts between government, private sector, and healthcare providers are essential to overcome these barriers. In conclusion, innovation in healthcare management must be holistic—integrating technological advancements with human, organizational, and policy-level adaptations—to ensure the delivery of high-quality, efficient, and sustainable healthcare services in the digital age.